The Role of Financial Knowledge and Adoption of Fintech Payment on MSME Performance in Bandar Lampung City - Annisa, Dwike Yuli; Amna, Luke Suciyati (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
This study aims to test the influence of Financial Knowledge and Fintech Implementation Payment on the Performance of Micro, Small and Medium Enterprises (MSMEs) in Bandar Lampung City. The research sample consisted of 100 MSMEs obtained through Slovin's estimation. The variables analyzed included Financial Knowledge as an understanding of basic financial concepts and Fintech Payment which includes the use of digital payment technology in business transactions. Multiple receivable analysis method used to see the influence of the two variables on the performance of MSMEs. The results of the study show that partially Financial Knowledge positive influence but not significant towards MSME performance, while Fintech Payment has a positive and significant influence on the performance of MSMEs. In addition, both variables simultaneously have a positive influence which is significant to the performance of MSMEs. The findings show that the implementation of Fintech Payment plays a bigger role in increasing the efficiency and effectiveness of MSME operations compared to the level of Financial Knowledge possessed by MSME actors. Therefore, this study suggests increasing financial literacy and adopting digital payment technology as a strategy to encourage the development of MSMEs in Bandar Lampung City.